The Evolving Landscape of Real Sector Halal Industry Research: A Bibliometric Approach - Rahma, Sakina Nur; Cahyadi, Ady (Maliki Islamic Economics Journal, 2024)
This study aims to analyze research trends on the real sector halal industry. This research uses bibliometric analysis which focuses on performance analysis and knowledge mapping. The database used is Scopus with a total of 632 metadata. The main software used for analysis is VOSviewer and Biblioshiny. The results of the analysis stated that research on the real sector halal industry began in 1994 and experienced the highest publication in 2023 with 105 publications. The best collaboration between countries is the collaboration between Malaysia - Indonesia. The influential author in real sector halal industry research is Mohd Helmi Ali and the country that is the leader of real sector halal industry research is Malaysia. The topic that is the main focus of discussion in the real sector halal industry in the global scope is halal food. Topic that has the potential to be developed in future research is the implementation of blockchain, especially in halal tourism.